Moral Challenges and Technological Prospects of Computerized Ifá Divination - Fayemi, Ademola Kazeem (Zygon, 2025)
Though there is an increasing interest in computerizing Ifá divination as a way of promoting accessibility, little is known about the moral and epistemic challenges linked to such digital feats. The technological breakthrough of computerized Ifá divination generates some dilemmas and poses some moral and epistemic challenges deserving critical interrogation. Through conceptual and empirical approaches, this research exposes some moral dilemmas at the intersection of spirituality and digital technology. Specifically, the research adopts a qualitative methodology with thematic analysis. It uses a deductive approach to engage with three dilemmas related to the moral and technological prospects of computerized Ifá divination. Data were gathered from structured interviews with seven Ifá priests in Lagos, Ibadan, Osogbo, Ife, and Ogun states in southwest Nigeria. Their responses were analyzed based on (1) whether to embrace automated divination amidst the potential climate of misuse of the Ifá corpus; (2) whether to accept computerized divination, which may devalue its rich spiritual recommendations for purposeful living; and (3) whether Ifá should be made publicly available through digital applications. The findings show the respondents are divided over Ifá digitization. Whereas some see it as a welcome development and advancement between technology and spirituality, others decry it.